Platelet Protease Activated Receptor 1 Is Involved in the Hemostatic Effect of 20(S)-Protopanaxadiol by Regulating Calcium Signaling - Zhang, He; Pan, Daian; Wu, Xingquan; Su, Wenjie; Tang, Xiaolei; Zhao, Daqing; Sun, Liwei; Song, Bailin; Bai, Xueyuan; Li, Xiangyan (Frontiers in Pharmacology, 2020)
Panax notoginseng (Burk.) F.H. Chen has long been used to stop bleeding for hundreds of years in China. At present, only dencichine, notoginsenoside Ft1, and 20(S)-protopanaxadiol (PPD) showed hemostatic effect. However, the molecular mechanism of PPD on the platelet aggragetion needs to be further investigated. The study aims to evaluate the hemostatic effect of PPD and reveal its interacting targets using a series of experiments. In this study, the bleeding time was measured in mouse tail amputation and liver scratch models to evaluate hemostatic effect of PPD. The routine blood and plasma coagulation parameters in NS, HC, and PPD (2, 4, and 8 mg/kg) groups were measured using a blood analyzer. Platelet aggregation rate and ATP release were analyzed by a platelet aggregometer. Subsequently, the degranulation marker CD62P and PAC-1, and the concentrations of cytosolic Ca2+ ([Ca2+]i), cAMP, cGMP, and PAC-1 expressions were also assessed. We found that PPD shorted the bleeding time on the mouse tail amputation and liver scratch models and mainly increased blood platelet count in the rats after subcutaneous injection for 4 h. Meanwhile, PPD decreased APTT, increased FIB content, and directly induced platelet aggregation in vitro. In the absence of Ca2+, PPD induced the increase of [Ca2+]i and slightly increased the levels of CD62P and PAC-1. After the addition of 1 mM Ca2+, PPD treatment markedly promoted platelet activation by promoting ATP level, releasing CD62P and increasing PAC-1 binding in washed platelets. Excitingly, PPD-induced changes including platelet aggregation, decreased cAMP content, and the increases of CD62P and PAC-1 were significantly reversed by protease-activated receptor 1 (PAR-1) antagonist, vorapaxar, which showed similar function as thrombin. In addition, molecular docking analysis and ELISA assay demonstrated that PPD had a promising docking score with -6.6 kcal/mol and increased PAR-1 expression in human platelets, which indicated that PAR-1 is involved in PPD-induced platelet aggregation by regulating calcium signaling. Collectively, our study could provide the new insights of PPD as an essential hemostatic ingredient in Panax notoginseng for the treatment of hemorrhagic disease.